Partisipasi laki-laki dalam program Keluarga Berencana di era masyarakat postmodern - Sutinah Sutinah (Faculty of Social and Political Science, Universitas Airlangga, 2017)
This study is motivated by the low number of men who become KB acceptor, although family planning programs have been promoted in Indonesia since the 1970s. Therefore, this study aims to examine: (1) men’s participation in the implementation of Family Planning Program in East Java Province; (2) obstacles that impede the participation of men in the implementation of the Family Planning Program; And (3) Strategies that need to be developed to increase men’s participation in the implementation of family planning programs in the postmodern society. This study was conducted in Surabaya which was choosen for representing the urban and Madiun for representing the character of rural communities. Samples was choosen in each city/district consists of 75 people or a total of 150 men. Data was collected through structured interviews with 15 informants are underwent indepth interview. This study found that (1) male participation in family planning in particular the use of vasectomy methods is still very low in both Surabaya and Madiun, most EFAs place family planning programs as women’s responsibilities; (2) obstacles that impede the participation of men in family planning are psychological constraints such as concern in decreasement in masculinity, impotence, social constraints; and the constraints that come from the wife such as possibility of wife’s affair; and (3) strategies for increasing men’s participation in family planning include more intensive socialization, and mass media campaigns, which feature popular ad stars, so the participation of men in the Family Planning Program is no longer considered something which is taboo or embarrassing.